Health-endangering everyday settings and practices in a rural segregated Roma settlement in Slovakia: A descriptive summary from an exploratory longitudinal case study - Andrej Belak; Andrea Madarasova Geckova; Jitse P. van Dijk; Sijmen A. Reijneveld (BMC, 2017)
Abstract Background Research into social root-causes of poor health within segregated Roma communities in Central and Eastern Europe, i.e. research into how, why and by whom high health-endangering settings and exposures are maintained here, is lacking. The aim of this study was to assess the local setup of health-endangering everyday settings and practices over the long-term in one such community. It is the initial part of a larger longitudinal study qualitatively exploring the social root-causes of poor Roma health status through the case of a particular settlement in Slovakia. Methods The study, spanning 10 years, comprised four methodologically distinct phases combining ethnography and applied medical-anthropological surveying. The acquired data consisted of field notes on participant observations and records of elicitations focusing on both the setup and the social root-causes of local everyday health-endangering settings and practices. To create the here-presented descriptive summary of the local setup, we performed a qualitative content analysis based on the latest World Health Organization classification of health exposures. Results Across all the examined dimensions - material circumstances, psychosocial factors, health-related behaviours, social cohesion and healthcare utilization - all the settlements' residents faced a wide range of health-endangering settings and practices. How the residents engaged in some of these exposures and how these exposures affected residents' health varied according to local social stratifications. Most of the patterns described prevailed over the 10-year period. Some local health-endangering settings and practices were praised by most inhabitants using racialized ethnic terms constructed in contrast or in direct opposition to alleged non-Roma norms and ways. Conclusions Our summary provides a comprehensive and conveniently structured basis for grounded thinking about the intermediary social determinants of health within segregated Roma communities in Slovakia and beyond. It offers novel clues regarding how certain determinants might vary therein; how they might be contributing to health-deterioration; and how they might be causally inter-linked here. It also suggests racialized ethnically framed social counter-norms might be involved in the maintenance of analogous exposure setups.